2004
DOI: 10.1080/00016350310008689
|View full text |Cite
|
Sign up to set email alerts
|

Eight‐year study on conventional glass ionomer and amalgam restorations in primary teeth

Abstract: The aim of this randomized clinical study was to compare the longevity and the cariostatic effects of conventional glass ionomer and amalgam restorations in primary teeth placed in everyday practice in the Danish Public Dental Health Service. All restorations inserted during a 7-month period by 14 clinicians in 2 municipalities were included in the study. The sample consisted of 515 conventional glass ionomer restorations and 543 amalgam restorations in 666 children aged between 2.8 and 13.5 years. The restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 15 publications
4
49
0
5
Order By: Relevance
“…23 The difference between both materials regarding the numbers of carious lesions of multiple-surface GIC restorations in primary teeth after three years was not statistically significant (OR 2.00; 95% CI 0.06-5.06; p = 0.10) but tended to favour GIC. 23 This trend was confirmed when the three-year results were combined with data from an eight-year study 24 using meta-analysis (OR = 2.35; 95% CI 1.18-4.71; p = 0.02). 23 …”
Section: Caries-preventive Effect: Glass-ionomer Cement Compared Withmentioning
confidence: 59%
“…23 The difference between both materials regarding the numbers of carious lesions of multiple-surface GIC restorations in primary teeth after three years was not statistically significant (OR 2.00; 95% CI 0.06-5.06; p = 0.10) but tended to favour GIC. 23 This trend was confirmed when the three-year results were combined with data from an eight-year study 24 using meta-analysis (OR = 2.35; 95% CI 1.18-4.71; p = 0.02). 23 …”
Section: Caries-preventive Effect: Glass-ionomer Cement Compared Withmentioning
confidence: 59%
“…The mean values for annual rates of caries progression for the current treatments assumed in the industry submission, along with the study reference from which these values were obtained, are: noncavitated pit and fissure caries 0%, 67 cavitated pit and fissure caries 4.9%, [68][69][70] and root caries 3.9%. 68,69 The progression rates cited for HealOzone were all 0%, taken from studies with follow-up of 3-21 months. 35,40,42,44,53,71,72 Caries reversal rates for non-HealOzone treatments were assumed to be zero.…”
Section: Summary Of the Industry Submissionmentioning
confidence: 99%
“…When glass ionomer is used as a material in the sealants, it exhibits the property of fluoride release. Consequently, fluoride release by glassionomer cement restorations ensures an anticariogenic effect around the enamel and in adjacent teeth [1][2][3][4] . Koga et al reported that glass-ionomer sealants had the highest fluoride release and recharge in distilled water among four different types of sealants and that the conventional resin-based sealants did not show fluoride recharge 5) .…”
Section: Introductionmentioning
confidence: 99%